Family Empowerment Model on Sensitive Nutrition Intervention for Stunting - Uswatun Khasanah; Esyuananik Esyuananik; Melyana Nurul W.; Anis Nur Laili; Nur Lailis Saadah; Patcharanee Pavadhgul (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Stunting is the result of chronic nutritional problems as a result of poor quality food, coupled with morbidity, infectious diseases, and environmental problems. The family is the first and foremost social environment for the growth and development of children. Children will develop optimally if they get good stimulation from the family. Sensitive nutrition interventions include 12 things that families and communities can do to deal with stunting in toddlers. This study aims to develop a family Empowerment model for sensitive nutrition interventions for stunting. The study was conducted in April-June 2022 with a quasi-experimental design and non-randomized pre-post control group design, with a sample size of 170 respondents who met the inclusion criteria. The family empowerment model is formed from the wife's age at marriage, husband's age at marriage, length of marriage, wife's education, number of children, family type, availability of facilities, knowledge, attitudes and behavior. The characteristics of respondents and the availability of facilities need to be considered in family empowerment. Family behavior in handling stunting through sensitive nutrition interventions will be formed if it is based on good knowledge and the availability of adequate facilities.